Характеристика та основні принципи сучасної освітньої парадигми - Агаларова, Карина Адільївна (Класичний приватний університет, 2018)
У статті розглядаються основні тенденції між сформованими традиціями в українській вищій школі та новими віяннями, пов’язаними зі вступом у світовий освітній простір. Зазначається, що головна мета інноваційної освіти – збереження і розвиток творчого потенціалу людини та підкреслюється, що головний принцип інноваційної освіти полягає в тому, що вона спрямована на формування світогляду, основаного на багатокритерійності рішень, терпимості до інакомислення й відповідальності за свої дії. У статті наголошується, що нова освітня парадигма як пріоритетне завдання освіти (загальної, середньої та вищої) передбачає орієнтацію на інтереси особистості, адекватні сучасним тенденціям суспільного розвитку. Також, у статті перераховуються основні пріоритетні напрями державної політики в галузі освіти. Розкрито сутність засад Національної доктрини освіти та її концептуальні положення. Підкреслюється важливість Національної доктрини освіти у переході до нового типу освіти.

The urgent task of sociology is the development of the concept of modernization of the domestic system of education and its content. The National Doctrine for the Development of Education of Ukraine outlined the long-term priorities of education and identified the ways of its transformation, where education is of primary importance as a factor in the development of the individual. This requires a profound analysis of the major changes in the field of education in the context of sociological science, which are conditioned by social changes – the transition from industrial to postindustrial, information society, which becomes more human centered, since individual development is not only an indicator of progress, but also a prerequisite for future development of society. Since education provides individual development of a person, it is important to transform it in the context of the requirements and capabilities of the XXI century. The article deals with the main tendencies between the established traditions in the Ukrainian high school and the new trends connected with entering the world educational space. It is noted that the main objective of innovation education – the preservation and development of creative potential of man and emphasizes the main principle of innovation education is that it is aimed at forming a worldview based on multi-criterion solutions, tolerance to dissent and responsibility for their actions. The article emphasizes that the new educational paradigm as a priority task of education (general, secondary and higher) presupposes an orientation towards the interests of the individual, which are adequate to the modern tendencies of social development. It is noted that the new educational paradigm provides for the acquisition of competence, erudition, creativity, and personality culture in relation to higher education. In this, her main difference from the old paradigm, which was generally aimed at learning (its slogans were: knowledge, skills, skills and upbringing). Also, the article lists the main priorities of the state policy in the field of education. The essence of the principles of the National Doctrine of Education and its conceptual provisions is revealed. Emphasizes the importance of the National Doctrine of Education in the transition to a new type of education.
Characteristics and basic principles of the modern educational paradigm
Keywords: освіта; національна доктрина; інтереси особистості; інноваційна освіта; education; educational paradigm; national doctrine